Can a positive doctor-patient relationship contribute to risk of elder abuse?. Issue 4 (7th August 2020) - Yaffe, Mark
ABSTRACT: Positive doctor-patient relationships have been noted to be possible facilitators in the identification of elder abuse. A case from family practice is cited in which an enduring and well-appreciated relationship unintentionally set up potential for mistreatment. Considerations to factors beyond traditional elder abuse risk factors should be kept in mind.